Instilling Character Value Of Cooperation Through Traditional Game In SD Negeri Mejasem Barat 03 Tegal Regency - Akhmad Junaedi; Tri Astuti (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
Traditional games are one of the wealth of the Indonesian nation that must be preserved.Conservation efforts can be implemented in schools. The main target iselementary school students because theyhave no difficulty getting to know the culture at this age.Traditional games can also be used to instil the character value of cooperation in groups. This value is beneficial for them in facing global challenges in society. The research method is qualitative because the data to be obtained is in the form of words and sentences from the object of research. This data describes how students show a cooperative attitude at school.This collaboration will be seen after the researcher introduces traditional games to students. They will then practice it with their classmates. Data were collected using observation, interview, questionnaire and documentation. The validity of the data was checked by triangulation of sources and methods. The process of instillingthe character value of cooperation in elementary students through traditional games experienced certain obstacles, but these obstacles could be overcome by collaborating with various parties such as students, parents and teachers.